Improving the technique of protecting concrete floors in poultry houses - Fotina, Tatiana; Petrov, Volodymyr; Havryliuk, Hryhorii; Liashenko, Yurii; Varenyk, Liudmyla (Eastern-European Journal of Enterprise Technologies, 2023)
The object of the study was concrete floors in a poultry house with different types of litter. The paper addressed the problem of reducing microorganism contamination of concrete floors in poultry houses to prevent biological corrosion. Corrosion of the surface of the concrete floor in the form of the formation of calcium oxalate monohydrate crystals was established by scanning electron microscopy; microscopic fungi: A. pullulans, F. sporotrichioides, and A. niger were detected. The TPD MS method established that concrete samples obtained in a room with straw lose moisture by 51.52 % more, with granules – by 342.42 % (р≤0.05), with shavings by 6.06 %, compared to control. CO from concrete samples is released less with sawdust litter by 86.40 %, with straw – by 83.49 %, with shavings – by 76.69 %, with granules – by 69.90 % (р≤0.05). The CO2 content in concrete samples from the room with sawdust was lower by 86.88 % (р≤0.05), with straw – by 55.73 %, with shavings – by 38.52 %, with granules – by 23.77 %, compared to control without litter. Microbiological studies have established that 48 hours after disinfection, the total number of colonies of microorganisms on a concrete floor with a sawdust litter likely decreased by an average of 90.19 %, straw – by 91.62 %, shavings – by 79.76 %, granules – by 82.88 % (р≤0.05), in the control – by 83.73 %. It can be argued that the disinfectant destroys microorganisms on the concrete surface regardless of the type of substrate. The peculiarity of the experiment was the use of scanning electron microscopy and TPD MS methods to study structural changes in concrete. The research is distinguished by the use of a powdered disinfectant to reduce microbial damage to a concrete floor with different types of litter. The results of the experiment could be used in the aggressive environment of poultry houses to reduce the impact on concrete structures